183. Retrospective analysis of Tomotherapy dose-of-the-day: Results and effectiveness on adaptive strategies. (December 2018) - Moretti, R.; Toraci, C.; Polonini, A.; Altabella, L.; Saiani, F.; Pegurri, L.; Buglione, M.; Spiazzi, L.
Abstract: Purpose: Analysis of dose-of-the-day (DoDa) for patients during treatment represents the first step to Adaptive-radiotherapy (ART). In our Institute DoDa for Tomotherapy plans is computed for first fraction for all patients, daily for SRT, weekly for all other treatments. This workflow aiming to ensure a control of delivered dose, check inter-fraction patient set-up and follow patient anatomical changes that may require a replanning. In this work we retrospectively reviewed DoDa of last 100 therapy courses in order to have an insights of efficacy and effectiveness of procedure. Methods: Patients included were 83. For each patient the associated plans (different courses and corresponding adaptive plans) were included (total of 137 plans included). For each plan, delivered fractions number, computed DoDa number, DoDa passed and failed numbers were reported. Results: 1507 delivered fraction were considered, 23% were checked computing DoDa. Passing rate was 78%. 10.9% DoDa outlined problems that need a plan reevaluation, while 10.3% showed problems of set-up but doses were adequately comparable to planned dose. All results are summarized in table. Conclusions: Although DoDa analysis process is demanding in terms of workload and computation time, our results show that may have a high impact on daily dose delivery quality shifting the paradigma from planned dose to actual delivered dose.